KESIAPAN PESERTA DIDIK MENUJU PROGRAM KERJA KE JEPANG (STUDI KASUS LPK MIRAI JAYA KECAMATAN INDRALAYA) - Winda Pitria Ayumiah; Ardi Saputra; Azizah Husin; Erna Retna Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the work readiness of trainees in preparing for employment programs in Japan at LPK Mirai Jaya, Indralaya. The background of this study is the gap between the competencies of Indonesian workers and the demands of the international labor market, particularly in Japan. This research used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving seven informants consisting of the head of the institution, an instructor, and trainees. The results show that trainees’ work readiness is reflected in four aspects: personal characteristics, organizational understanding, work competence, and social intelligence. Trainees generally demonstrate increased confidence, discipline, and motivation. However, challenges remain in adapting to strict discipline and intensive training. The study concludes that LPK plays a significant role in improving trainees' readiness through structured training programs focusing on language skills, work discipline, and character building.